The Mediating Role of Brand Image in the Relationship Between Fan Engagement and Fans' Attitudinal and Behavioral Loyalty - Mostafavipour , Shimasadat; Sadjadi Hezaveh , Seyyed Hamid; Haji Anzehaei , Zahra (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The aim of this study was to investigate the mediating role of brand image in the relationship between fan engagement and fans' attitudinal and behavioral loyalty.Methodology: In this correlational study, the statistical population consisted of fans of the Iranian Premier Football League. Among them, four teams (Persepolis, Esteghlal, Tractor, and Sepahan) were selected as the top four teams of the 2019-2020 season. Given the unlimited size of the statistical population, stratified random sampling was employed, and the sample size was determined to be 258 individuals. Data were collected using the Fan Engagement with Brand Questionnaire by Desar (2017), the Team Brand by Bauer et al. (2008), and Fan Loyalty, including Attitudinal Loyalty and Behavioral Loyalty (Gladden & Funk, 2001; Stevens & Rosenberger, 2012; Wang et al., 2011). Pearson correlation coefficient and structural equation modeling were used for data analysis.Findings: Fan engagement influences the team’s brand image, and brand image affects both attitudinal loyalty and behavioral loyalty. This study also demonstrated that brand image plays a mediating role in the relationship between fan engagement with the brand and fans' attitudinal and behavioral loyalty.Conclusion: The present study contributes to filling the gap in sports marketing literature by providing a better understanding of what contributes to fan loyalty for professional football teams in the Iranian Premier League. Building on existing sports marketing literature, the model developed in this study enables sports managers to comprehensively measure the relationships between fan engagement, team brand image, attitudinal loyalty, and behavioral loyalty.